Profits, Wages and Inflationary Dynamics in the Euro Area and the US in the Context of Uncertainty - Stefan Collignon (London School of Economics and Political Science (LSE), European Institute, 2023)
A sequence of severe shocks has brought inflation back to Europe and America, but unemployment is still at record low levels. Is higher unemployment required to bring inflation down? The challenges are the same for both economies across the Atlantic, the policy tools resemble each other, but they apply to different economic landscapes. What can we learn from each other? Who has been more successful? The paper looks at basic facts, the nature of shocks, and the efficiency of policy tools. It turns out that the Phillips curve whereby higher unemployment lowers inflation has a different role in Europe than in the US. The key to understanding recent developments is uncertainty. The paper extends the standard New Keynesian model to measures of uncertainty. It argues that the channel through which uncertainty influences inflation, wage cost and unemployment is the markup firms charge to cover their cost of capital. The Federal Reserve Bank has been more successful because it operates in a more competitive market for goods and capital. The Euro Area lacks a fully integrated capital market with a benchmark euro bond and the institutions for setting up a coherent macroeconomic policy stance. This will make disinflationin Europe more painful in terms of unemployment.
Keywords: 330